2007
DOI: 10.1124/jpet.107.131433
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Nicotinamide Adenine Dinucleotide Phosphate Oxidase Expression and Function by 3′,4′-Dihydroxyflavonol in Phagocytic and Vascular Cells

Abstract: Previously we have demonstrated that 3Ј,4Ј-dihydroxyflavonol (DiOHF), a novel synthetic flavonol, protects against ischemia reperfusion injury in both heart and brain. In this study, we characterized the pharmacological effects of DiOHF on phagocytic and vascular NADPH oxidase. Superoxide release (lucigenin-enhanced chemiluminescence or cytochrome c reduction), NADPH oxidase activation (membrane translocation of p47phox), and subunit expression (real-time polymerase chain reaction and Western blot) were examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 27 publications
4
27
0
Order By: Relevance
“…Although we don't have any direct evidence for such actions by DiOHF, quercetin, a major dietary catechol-containing flavonoid similar in structure to DiOHF, has been reported to down-regulate NADPH oxidase-mediated O 2 − generation in hypertensive rats, and to increase Mn-SOD protein expression in parenchymal liver cells induced by proinflammatory stimuli (Crespo et al 2008;Romero et al 2008;Sanchez et al 2006). Recently, it has also been reported that DiOHF decreased NADPH oxidase-mediated O 2 − generation in HL-60 cells, associated with reduced p47phox expression (Jiang et al 2008). Thus, DiOHF may have a genomic action, which develops over days and results in a prolonged antioxidant action in addition to an ability to scavenge oxygen radicals observed upon acute exposure.…”
Section: Discussionmentioning
confidence: 94%
“…Although we don't have any direct evidence for such actions by DiOHF, quercetin, a major dietary catechol-containing flavonoid similar in structure to DiOHF, has been reported to down-regulate NADPH oxidase-mediated O 2 − generation in hypertensive rats, and to increase Mn-SOD protein expression in parenchymal liver cells induced by proinflammatory stimuli (Crespo et al 2008;Romero et al 2008;Sanchez et al 2006). Recently, it has also been reported that DiOHF decreased NADPH oxidase-mediated O 2 − generation in HL-60 cells, associated with reduced p47phox expression (Jiang et al 2008). Thus, DiOHF may have a genomic action, which develops over days and results in a prolonged antioxidant action in addition to an ability to scavenge oxygen radicals observed upon acute exposure.…”
Section: Discussionmentioning
confidence: 94%
“…The NOX activity was expressed as relative light units per milligram of cellular protein in cells or aortic rings. Superoxide production was normalized to the weight of dried aortic tissue samples (39,74).…”
Section: Methodsmentioning
confidence: 99%
“…NOX activity in cells or mouse aortic rings was measured by lucigenin-enhanced chemiluminescence (39,40,52). In brief, confluent ECV304 cells or mouse aortas, cleared of adherent fat and cut into 2-mm rings, were preincubated for 45 min at 37°C in Krebs-HEPES buffer (99 mM NaCl, 4.7 mM KCl, 1 mM KH2PO4, 1.2 mM MgSO4, 2.5 mM CaCl2, 25 mM NaHCO3, 20 mM Na-HEPES, and 11 mM glucose, pH 7.4) containing 100 M of NADPH, with or without 1 mM apocynin (SigmaAldrich, St. Louis, MO), or EGFR inhibitor AG1478 (Calbiochem, La Jolla, CA).…”
Section: Methodsmentioning
confidence: 99%
“…NBT reduction to formazan has been previously used as a marker for nicotinamide adenine dinucleotide phosphate (NADPH) oxidase (Jiang, 2008 ). Parental U937 cells and stable clones (UN5, UG6, and UG11), at a density of 10 6 , were incubated with 0.2% NBT (Sigma), dissolved in PBS, for 30 min at 37°C in a 5% CO 2 -incubator.…”
Section: Morphological and Flow Cytometric Analysis And Enzymatic Stmentioning
confidence: 99%
“…Functional differentiation of monoblasts into monocytes was histologically quantified by the cell's ability to produce a superoxide, generated via NADPH oxidase, and to reduce the tetrazolium salt NBT to insoluble formazan, which forms a black-blue precipitate in these cells (Jiang et al, 2008). As shown in Figure 3, NBT-reducing ability was enhanced in UG6 (70%) and UG11 (68%) cells, when compared with UN5 (2%) and parental (2%) cells ( Figure 3B).…”
Section: Induction Of Monocytic Differentiation Markers In Gelsolinovmentioning
confidence: 99%